BALANCED SCORECARD: FOKUS PADA PERSPEKTIF PELANGGAN: Studi Empiris di Ponpes - Machmuddah, Zaky; Utomo, St. Dwiarso; Setiawanta, Yulita (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The aim of the research is to find an empirical evidence concerning the implementation of customer perspective of Balanced Scorecard (BSC) in Assalaam Islamic Modern Boarding School Surakarta (AIMBS Surakarta). It is a case study research. Qualitative research design is conducted using semi-structured interviews with 27 members from different stakeholders. Research findings showed that customer perspective of BSC and attributes in strategy map of BSC have been implemented well in AIMBS Surakarta. Besides, the research found supporting factor of implementation of customer perspective of BSC in AIMBS Surakarta, namely: strong commitment from management to adjust the change. The limitation of the research is that the research findings can not be generalized. For future research, it is suggested that the researcher will add the numbers of research object so that the generalization of the research findings can be achieved. Thus, it will give clearer description about implementation of customers perpective of BSC in Islamic boarding schools